Increased Levels of Umbilical Cord Blood Interleukin-6 (IL-6) and Serum C-Reactive Protein (CRP) in Premature Infants of Vitamin D Deficient Mothers: Peningkatan Kadar Interleukin-6 (IL-6) Darah Tali Pusat dan Serum C-Reactive Protein (CRP) pada Bayi Prematur dari Ibu dengan Defisiensi Vitamin D - Yuyun Lisnawati; Marianna Yesy; Rinawati Rohsiswatmo (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objective: Increased levels of inflammatory factors in newborns are often associated with lower maternal vitamin D levels. This study aimed to find out the relationship between maternal and umbilical cord vitamin D serum levels on umbilical cord Interleukin-6 (IL-6) and serum C-Reactive Protein (CRP) levels in premature infants.Methods: The study was an observational analytic, cross-sectional design in mothers who underwent preterm birth at 28-34 weeks' gestation due to premature rupture of membranes (PROM) and their infants at Dr. Cipto Mangunkusumo General Hospital (RSCM), Jakarta and Persahabatan General Hospital, Jakarta, from January 2017 to August 2018. Levels of serum vitamin D of the maternal and umbilical cord, umbilical cord IL-6 and serum CRP in premature infants were recorded. Vitamin D level was divided into deficiency (<10 ng/mL), insufficiency (10–29 ng/mL), and normal (>30 ng/mL) groups. The relationship of vitamin D levels with IL-6 and CRP was carried out using Kruskal Wallis test.Results: A total of 70 subjects met the research criteria. Umbilical cord IL-6 and serum CRP levels in premature infants of vitamin D deficient mothers were higher (20.31 pg/mL and 0.50 mg/L) compared to insufficient (3.34 pg/mL and 0.45 mg/L) and normal mothers (3.29 pg/mL and 0.30 mg/L), although not statistically significant (IL-6 p = 0.665, CRP p = 0.89). Referring to the umbilical cord blood vitamin D levels, the results were different and not as expected, in which the umbilical cord IL-6 and serum CRP levels of preterm infants in the deficiency (3.76 pg/mL and 0.35 mg/L) and insufficiency (3.37 pg/mL and 0.40 mg/L) groups were lower (IL-6) and not different (CRP) than the normal group (9.41 pg/mL and 0.40 mg/L).Conclusion: There were an increasing tendency for umbilical cord IL-6 and serum CRP levels in premature infants of vitamin D deficient mothers although these were not statistically significant. Based on the levels of vitamin D umbilical cord blood, the CRP levels in the serum of premature infants were not different, while the IL-6 levels in the deficiency and insufficiency group were lower than in the normal group.Keywords: CRP, IL-6, maternal vitamin D, umbilical cord vitamin D. Abstrak Tujuan: Peningkatan kadar faktor inflamasi pada bayi baru lahir sering dikaitkan dengan rendahnya kadar vitamin D ibu. Penelitian ini bertujuan untuk mengetahui hubungan kadar serum vitamin D ibu dan tali pusat, dengan kadar IL-6 tali pusat dan serum C-Reactive Protein (CRP) bayi prematur.Metode: Studi observasional analitik dengan desain potong lintang pada subjek ibu yang mengalami kelahiran prematur di usia 28–34 minggu kehamilan disebabkan ketuban pecah dan bayi yang dilahirkannya, di Rumah Sakit Umum Pusat Nasional dr. Cipto Mangunkusumo (RSCM) dan Rumah Sakit Umum Pusat Persahabatan, Jakarta, pada bulan Januari 2017 sampai Agustus 2018. Variabel data adalah kadar serum vitamin D ibu dan tali pusat, kadar serum IL-6 tali pusat dan kadar CRP darah bayi. Kadar vitamin D (25(OH)D) dibagi menjadi defisiensi (<10 ng/mL), insufisiensi (10–29 ng/mL) dan normal (>30 ng/mL) dan dicari hubungannya dengan kadar IL-6 tali pusat dan serum CRP bayi prematur, menggunakan uji Kruskal Wallis. Hasil: Sebanyak 70 subjek telah memenuhi kriteria penelitian. Kadar IL-6 tali pusat dan serum CRP bayi prematur dari kelompok ibu defisiensi vitamin D (20,31 pg/ml dan 0,50 mg/L) lebih tinggi dibandingkan kelompok ibu insufisiensi vitamin D (3,34 pg/mL dan 0,45 mg/L) maupun kelompok ibu normal vitamin D (3,29 pg/mL dan 0,30 mg/L) tetapi perbedaan tersebut tidak bermakna (IL-6 p=0,665 dan CRP p = 0,899). Mengacu pada kadar vitamin D darah tali pusat didapatkan hasil yang berbeda dan tidak sesuai harapan, dimana tali pusat IL-6 dan serum CRP bayi prematur mengalami defisiensi (3,76 pg / mL dan 0,35 mg / L) dan insufisiensi. (3,37 pg / mL dan 0,40 mg / L) kelompok lebih rendah (IL-6) dan tidak berbeda (CRP) dibandingkan kelompok normal (9,41 pg / mL dan 0,40 mg / L).Kesimpulan: Didapat kecenderungan peningkatan kadar IL-6 darah tali pusat dan serum CRP bayi prematur dari ibu dengan defisiensi kadar vitamin D walaupun secara statistik tidak signifikan. Berdasarkan kelompok vitamin D darah tali pusat, kadar CRP serum bayi prematur tidak berbeda, sedangkan kadar IL-6 pada kelompok defisiensi dan insufisiensi lebih rendah dibandingkan pada kelompok normal.Kata kunci: CRP, IL-6, vitamin D ibu, vitamin D tali pusat.